Star Trek: Discovery [videorecording (DVD)] . Season 2 - Martin, Sonequa; Jones, Doug, 1960-; Rapp, Anthony (Paramount Home Entertainment, 2019)
After answering a distress signal from the U.S.S. Enterprise, the U.S.S. Discovery welcomes aboard Captain Christopher Pike and begins a new mission to investigate the meaning behind seven mysterious red signals. Michael Burnham grapples with her past growing up on Vulcan with her foster parents and brother Spock.